Climate change adaptation on rice production - Navya M (Academy of Climate Change Education and Research, 2016)
The impacts of climate change on agriculture are global concerns and for that matter India, where agriculture sector alone represents 23 per cent of India’s Gross National Product (GNP) and the livelihood of nearly 70 per cent of the population is exposed to a great danger, as the country is one of the most vulnerable countries due to climate change. One of the most notable characteristics of climate change is the increase in temperature, so it has been mainly recognized as ‘global warming’. The conclusions of the Fourth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC) published in early 2007 leave no doubt that the Earth’s climate is changing in a manner unprecedented in the past 400,000 years. The report substantiated that by 2100 mean surface temperatures over the earth will rise by 1.4 to 5.8 ° C, precipitation will decrease in the sub-tropics, and extreme events will become more frequent (IPCC, 2007). However, changes in climate are already being observed and the last 60 years were the warmest in the last 1000 years and changes in precipitation patterns have brought greater incidence of floods or drought globally. Climate change has negatively affected India’s millions of rice producers and consumers. Harvest would have been 5.67 per cent higher in the absence of climate change. Future impacts of these changes on rice yield in India would thus likely be larger than the historical ones (Auffhammer et al., 2012). There is a huge gap between potential and actual grain yield of rice in Kerala. The growth and yield is largely depends on the various weather factors like temperature, rainfall, solar radiation and relative humidity that prevail during the growing season. Objectives of the study were to study the climate change adaptation in rice production through fertilizer management strategies and to determine the optimum sowing period in purview of climate change and temperature stress tolerance in popular rice varieties of Kerala using DSSAT model. The fileld experiments were conducted during April 2016 to September 2016 at the Regional Agricultural Research Station of the Kerala Agricultural University at Pattambi, Palakkad district, Kerala in variety Jyothi. The result showed that the dates of planting, fertilizer treatment and different growing environment had significance on yield of rice. The highest grain yield (6324.0 kg/ha) was recorded by crop transplanted on 1st May 2016 in the open field fertilizer application as per soil test result along with foliar application (19:19:19 NPK 5g at 15 days interval) and silica (1g per pot). Solar radiation, temperature, relative humidity and soil temperature are the major weather parameters that influence the yield and phenology of rice. Changes in fertilizer use, soil test based fertilizer recommendation, application of micronutrients and additional inputs like silica reduced the weather dependency in rice production. High temperature stress tolerance of the popular varieties of Kerala i.e., Jyothi, Kanchana, Athira, Vysakh and Jaya were worked out based on the past data generated as a part of various research programmes under KAU using DSSAT model. Variety Jyothi showed a very slight decrease in yield when the temperature was increased by 1°C, 2°C and 5°C. Compared to other varieties Jyothi showed high tolerance to temperature stress. Varieties like Kanchana, Athira and Jaya had showed continuous decrease in yield to 1°C, 2°C and 5°C increase in temperature whereas variety Vysakh showed an increase in yield up to 2°C increase temperature compared to the present condition but the yield were drastically reduced when the temperature was elevated to 5°C. Adjusting the planting time is considered one of the climate change adaptation strategy for improving the rice production. An attempt was made to quantify the impact of planting time on crop yield of variety Jyothi using DSSAT model. The observed and projected yield for the first crop season for the variety Jyothi showed more or less a continuous increase in yield starting from May 1st to August 1st. Crops planted on August 1st (6810 kg/ha) recorded the highest grain yield and the lowest was recorded during the May 15 planting (2212 kg/ha). During 2030, 2050 and 2080 showed a similar trend in the yield pattern corresponding to the above sowing periods. It is interesting to notice that the yields of crops planted during the month of May showing an increasing trend during 2030, 2050 and 2080 whereas the yields during the conventional sowing periods showed a declining trend. The yields of late planted crops will also going to increase as per the projected climate change scenarios, but it will prevent the possibility of second crop rice.